The Sensitivity of Orographic Precipitation to Flow Direction: An Idealized Modeling Approach - Picard, Lee Michael (My University, 2016)
A method is developed for forcing a full-physics, full-terrain model with an idealized, balanced atmosphere determined by an input sounding. The initialization technique is applied to investigate the sensitivity of orographic precipitation in Pacific Northwest terrain to wind direction under both barotropic and sheared flow conditions approximating an atmospheric river. The model results agree well with previous studies that considered typical conditions resulting in heavy precipitation, with the precipitation sensitivity to wind direction less than is estimated for similar deterministic cases. To explore the causes of sensitivity in the Olympic Mountains of western Washington State, additional experiments are carried out using modified terrain fields with smoothed or idealized Olympic Mountains, or with nearby orography removed. Model simulations suggest that the sensitivity of Olympic Mountain precipitation to wind direction is more strongly modulated by the presence of surrounding orography than by the specific Olympic geometry.
Thesis (Master's)--University of Washington, 2015
Keywords: idealized modeling; Olympic Mountains; orographic precipitation; Atmospheric sciences; Meteorology; atmospheric sciences